1991
DOI: 10.3109/00016489109138433
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of Ischemic Facial Nerve Paralysis in an Animal Model

Abstract: The establishment of an animal model for facial nerve paralysis is assuming increasing importance in clinical medicine and also in basic facial nerve research. We previously reported an animal model for ischemic facial nerve paralysis using selective vascular embolization through the internal maxillary and posterior auricular arteries in cats using Avitene which contains bovine microfibril collagen. In this paper, we determined the exact site of the lesion in established facial paralysis. A descending signal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The most likely cause of Bell's palsy is oedema of the facial nerve induced by the herpes virus and varicella zoster virus . Other suggested causes include ischaemia, autoimmune inflammatory disorders and heredity . Although the aetiology of Bells palsy is not clear, the facial weakness is thought to result from facial nerve inflammation and oedema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely cause of Bell's palsy is oedema of the facial nerve induced by the herpes virus and varicella zoster virus . Other suggested causes include ischaemia, autoimmune inflammatory disorders and heredity . Although the aetiology of Bells palsy is not clear, the facial weakness is thought to result from facial nerve inflammation and oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Later a secondary ischaemic theory is an inflammatory, viral or immunologic oedema causing disturbances of the microcirculation, leading to loss of nerve conductivity. Both concepts suggest that these processes lead to anoxia followed by compensatory dilation of the vessels and transudation …”
mentioning
confidence: 99%
“…An experimental animal model of ischemic facial palsy was first reported by McGovern et al 9,10 Ischemic facial palsy was induced by the injection of a vasoconstrictor into the facial canal. Iritani et al 11 and Kumoi et al 12 created a new ischemic animal model by the selective embolization of the middle meningeal artery in adult cats. Since this model was atraumatic and reproducible, it was widely applied to basic facial research.…”
Section: Discussionmentioning
confidence: 99%
“…Table I summarizes the results obtained from normal untreated animals, 15,16 animals in which facial palsy was experimentally induced, 11,12 and animals after reserpinization. In a previous study, Na‐K ATPase activity in normal guinea pigs 15 and cats 16 was found to be localized to the entire axolemma and to the Schmidt‐Lanterman incisures and terminal loops of Schwann cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation